Guidelines for the Development of Educational Institution Administration Based on the Principles of Good Governance under the Khon Kaen Primary Educational Service Area Office 3 - Sriuttha, Comkrit; Poomkong , Somsak; Siripoonyanan, Tanasak (Journal of Buddhist Education and Research (JBER), 2025)
The objectives of this research were to study: (1) the current conditions, the desired conditions, and the needs regarding school administration based on the principles of good governance in schools under the Office of Khon Kaen Primary Educational Service Area 3, and (2) guidelines for developing school administration according to the principles of good governance in schools under the same office. The research was divided into two phases. The first phase focused on investigating the current conditions, desired conditions, and needs, employing Krejcie and Morgan's table to identify a sample group of 297 teachers and school administrators. A questionnaire on a five-point Likert scale served as the research instrument. The index of item-objective congruence (IOC) ranged from 0.80 to 1.00. The discrimination power for each item regarding the current and desired conditions ranged from 0.40 to 0.86, and the reliability coefficient was 0.96. For the second phase, it involved developing guidelines for school administration based on good governance principles. This phase employed semi-structured interviews and an assessment form for evaluating the appropriateness and feasibility of the proposed guidelines. The data were analyzed using percentage, mean, standard deviation, the Modified Priority Needs Index (PNImodified), and content analysis. Experts in educational governance (nine in total, selected through purposive sampling) evaluated the proposed guidelines, which were found to be at the highest level of appropriateness and feasibility. The results of the research were as follows: 1. The results for current conditions, desirable conditions, and needs assessment for school administration based on good governance principles in schools under Khon Kaen Primary Educational Service Area Office 3 revealed that: The overall current conditions were at a high level (x̄= 4.10). When considered by aspect, it was found that the effectiveness principle was at the highest level (x̄= 4.29), and the equity principle was at the lowest level (x̄= 3.39). The overall desirable conditions for school administration based on good governance principles in schools under Khon Kaen Primary Educational Service Area Office 3 were also at the highest level (x̄= 4.80). When considered by aspect, it was found that the equity principle was at the highest level (x̄= 4.87), and the participation principle was at the lowest level (x̄= 4.75). According to the needs assessment for school administration based on good governance principles in schools under Khon Kaen Primary Educational Service Area Office 3, the accountability principle received highest ranking (PNIModified = 0.154), followed by transparency (PNIModified = 0.124), effectiveness (PNIModified = 0.119), rule of law (PNIModified = 0.116), participation (PNIModified = 0.112), and equity (PNIModified = 0.109), respectively. 2. The guidelines for developing school administration based on good governance principles in schools under Khon Kaen Primary Educational Service Area Office 3 consisted of 6 aspects: 1) Accountability with 3 guidelines, 2) Transparency with 3 guidelines, 3) Effectiveness with 3 guidelines, 4) Rule of Law with 3 guidelines, 5) Participation with 3 guidelines, and 6) Equity with 3 guidelines, totaling 18 guidelines. The appropriateness was at the highest level (x̄= 4.83), and the feasibility was at the highest level (x̄= 4.75).